Enhanced performance of new family Modified Double Weight codes spectral amplitude coding optical CDMA system network - Arief, A. R.; Aljunid, S. A.; Anuar, M. S.; Junita, M. N.; Ahmad, R. B.; Ghani, F. (2011 IEEE International Conference on Control System, Computing and Engineering, 2011)
A new family of spectral/spatial spectral amplitude-coding (SAC) optical code division multiple access (OCDMA) scheme using Modified Double Weight (MDW) code is developed. The new codes are derived from Modified Double Weight codes with good cross correlation. This proposed system can suppress the phase-induced intensity noise (PIIN) by using multiuser interference (MUI) cancellation property. The proposed 2-D OCDMA MDW can offer a much larger capacity compare to the 1-D OCDMA MDW Code.